Electronic Government 12th IFIP WG 8.5 International Conference, EGOV 2013, Koblenz, Germany, September 16-19, 2013. Proceedings - Wimmer, Maria A.; Janssen, Marijn; Scholl, Hans J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 12th IFIP WG 8.5 International Conference on Electronic Government, EGOV 2013, held in Koblenz, Germany, in September 2013. The 27 revised full papers presented were carefully reviewed and selected for inclusion in this volume. The papers have been organized in the following topical sections: research foundations; open government data and transparency; service design and improvement; adoption and service evaluation; and social media and social network analysis.
Research foundations -- Open government data and transparency -- Service design and improvement -- Adoption and service evaluation -- Social media and social network analysis.
Keywords: Computer science; Information systems; Computers -- Law and legislation; Computer Science; Computers and Society; Legal Aspects of Computing; Information Systems and Communication Service; Computer Appl. in Administrative Data Processing